NEO-SEISMOTEKTONIK SEMENANJUNG MANADO SULAWESI UTARA - S. Poedjopradjitno (Jurnal Geologi dan Sumberdaya Mineral, 2012)
Neo-Seismotectonic study of Manado Peninsula by using approach of geomorphology, geology data method and seismisity, obtained of picture in detail peninsula structure pattern and can interpret earthquake susceptable disaster zona. Such structure pattern is area grouped of peninsula structure become six domain structure, that is : Amurang domain structure (A), Soputan (S), Tondano (T), Manado (M), Likupang (L) and Batuangus ( BA).Based on susceptable the earthquake disaster matrix covering geomorfologi data, geology, ground and rock physical, tectonic indication, infrastructure, disaster potency and risk, peninsula area can divided to the three area susceptable to earthquake disaster namely high, middle and lower earthquake disaster susceptable zona.Key word :geomorphology, geology, seismicity and structure